2020
DOI: 10.3390/app10072246
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Properties of Cement Mortar Composite Containing Recycled Expanded Glass Aggregate and Nano Titanium Dioxide

Abstract: One of the growing concerns in the construction industry is energy consumption and energy efficiency in residential buildings. Moreover, management of non-degradable solid glass wastes is becoming a critical issue worldwide. Accordingly, incorporation of recycled expanded glass aggregates (EGA) as a substitution for natural fine aggregate in cement composites would be a sustainable solution in terms of energy consumption in the buildings and waste management. This experimental research aims to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The influence of different sizes of glass aggregates on the properties of self-compacting mortar was carried out by Ling and Poon [ 31 ]. Meanwhile, Yousefi et al [ 32 ] investigated the impact of different particle sizes of expanded glass aggregate (EGA) on the compressive strength. Bostaci et al [ 33 ] used 15% of glass sand from recycling with a particle size of up to 5 mm and obtained an 8.1% decrease in compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of different sizes of glass aggregates on the properties of self-compacting mortar was carried out by Ling and Poon [ 31 ]. Meanwhile, Yousefi et al [ 32 ] investigated the impact of different particle sizes of expanded glass aggregate (EGA) on the compressive strength. Bostaci et al [ 33 ] used 15% of glass sand from recycling with a particle size of up to 5 mm and obtained an 8.1% decrease in compressive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Silica aerogel is a lightweight thermal insulating material having low density and high specific surface area, allowing its application in many areas 20 . Expanded glass aggregates is also a thermal conducting material with porous structure 21 . Lightweight aggregates are 25–35% lighter than the conventionally used aggregates 19 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that an optimal graduating of lightweight aggregates could reduce the porosity of lightweight aggregate concrete and improve mechanical performance. Major studies have been presented on the use of lightweight aggregate such as fly ash 26 , 27 , expanded glass aggregate 28 , silica aerogel 21 in cement mortar. A study conducted by Yousefi et al 21 reported a decrease in compressive strength of cement mortar containing expanded glass aggregates, however inclusion of nano titanium dioxide as nanomaterials increased compressive strength by 39.02%.…”
Section: Introductionmentioning
confidence: 99%
“…Cast-in-place concrete provides a much wider range of concrete applications, e.g., wall structures, floor and road thermal insulation, and floor and roof screeds [13][14][15]. Light composites with foamed aggregates have extremely good thermal and acoustic insulation, fire resistance, and resistance to earthquakes compared to traditional concrete [16][17][18][19][20][21][22][23]. The good workability and fluidity of the concrete mix gives the opportunity to form unrestricted shapes.…”
Section: Introductionmentioning
confidence: 99%